Method for producing furfural and catalyst for use therein

JP2024513868A5Pending Publication Date: 2025-04-08MONASH UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023561007
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-01
Filing Date
2022-04-01
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Current methods for producing furfural from lignocellulosic biomass face challenges such as low yield, high corrosiveness of acids, difficult separation and recovery, and large wastewater volumes, along with the need for efficient recovery of valuable materials from waste tire products.

Method used

The use of solid zinc sulfate-rich catalysts, potentially doped with transition metals like palladium, for the pyrolysis of lignocellulosic materials to produce furfural, combined with a method to recover zinc sulfate from tire char, reducing the need for corrosive acids and minimizing wastewater.

Benefits of technology

This approach achieves high conversion rates and selectivity for furfural production while reducing corrosion and wastewater, and provides a method to recover valuable materials from tire char.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Provided herein is a method for producing furfural from lignocellulosic biomass or an extract thereof, such as a sugar-rich extract, using a solid zinc sulfate-rich catalyst that catalyzes the conversion to furfural. Also provided herein is a zinc sulfate-rich catalyst, and a method for producing zinc sulfate and the zinc sulfate-rich catalyst from tire char.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing furfural from lignocellulosic biomass or extracts thereof using a solid zinc sulfate-rich catalyst. The present disclosure also relates to the zinc sulfate-rich catalyst utilized in said method, and further to a method for producing zinc sulfate and the zinc sulfate-rich catalyst from tire char. [Background technology]

[0002] The production of value-added, renewable chemicals from lignocellulosic biomass is important for a smooth transition from the current economy to a carbon-neutral future. As a useful precursor and platform material for the synthesis of a wide range of end products, including pharmaceuticals, herbicides, stabilizers, and polymers, furfural is listed as one of the top 12 biomass-derived products recognized by the United States Department of Energy (DOE) [1,2]. Traditionally, furfural is produced from C5 hemicellulose by hydrolysis. Compared to the production of furfural from C5 hydrocarbons, the conversion of C6 sugars to furfural has not been successful due to the extremely low furfural yield of C6, which is due to the difference in composition and structure of C6 from C5 [1,3].

[0003] Solvothermal reactions, i.e., solvolysis or hydrolysis, have so far proven to be one of the most efficient approaches to improve the selectivity of biomass-derived chemicals [1,4]. In industry, furfural is currently produced from hemicellulose by using concentrated or dilute inorganic acids such as H2SO4, HCl and H3PO4 as catalysts, achieving furfural yields of 50% to 75% in water at typical temperatures ranging from 160 to 240 °C [1,5,6].

[0004] One such example is described in US Patent Application Publication No. 2011 / 0144359 [7], which provided a method for producing furfural from lignocellulosic biomass materials in a plug-flow reactor. In the best case scenario, 5 wt% xylose water was converted to 67.6 mol% furfural in 5.87 min using 0.5 wt% H2SO4 at 230 °C as a catalyst. The overall conversion of xylose was 98.78%. As a further example, US Patent Application Publication No. 2013 / 0109869 [8] introduced metal halides in a water-miscible solution for a similar method for producing furfural from lignocellulosic biomass. It was reported that under optimal conditions involving the use of 25% corn cob, 0.15 M H2SO4, and a mixed solvent of water (7.3 g) and tetrahydrofuran (THF, 42.0 g) and 1% NaCl in sodium chloride (0.7 g), at 160 °C and 30 min, the yield of furfural reached 87%.

[0005] More recently, US Patent Application Publication No. 2014 / 0171664 [9] claims a method for the production of furfural from xylan-containing lignocellulosic feedstocks. A mixture of corn cobs (16 g) and aqueous sulfuric acid solutions (6.4 g) of various pH values ​​were loaded into an autoclave and subjected to six temperature / pressure cycles consecutively. In the best case scenario, the use of an aqueous sulfuric acid solution with a pH of 0.50 resulted in a 68% furfural yield and complete conversion of xylan. Another study reported that the highest yield of furfural from glucose using modified Sn-beta zeolite as catalyst in gamma-valerolactone (GVL) solvent reached 0.69 mol / mol glucose at 180 °C for 33 min [1].

[0006] Despite its maturity as a process, solvolysis has many drawbacks that must be overcome, including the difficult and costly separation and recovery of furfural, the corrosive nature of inorganic acids, and the large amounts of wastewater resulting from their use.

[10]

[0007] Due to potential environmental and management challenges for the production of furfural, there remains a need to reduce the large amounts of acid currently used during the solvolysis process.

[0008] Worldwide, vehicle tires on an estimated 1.5 billion vehicles need to be replaced each year

[11] . Although some can be retreaded, many of these tires end up in landfills, and end-of-life vehicle tires represent a significant environmental challenge. For example, harmful tire components can leach into the surrounding environment, and piles of tires pose a fire risk.

[0009] Vehicle tires typically contain a complex mixture of materials including natural and synthetic rubber compounds, reinforcing compounds such as steel wire and polymeric fibers, plasticizers, fillers including carbon black and silica, and vulcanizing chemicals such as sulfur and zinc oxide compounds, which makes recovery and reuse of tire components difficult.

[0010] One approach that has been used to produce useful products from waste tires is pyrolysis of waste tires.

[12] Typically, this involves heating the tires at high temperatures in a reactor to produce components such as tire oil, char and gas products. However, there remains a need to find additional uses for waste tire products, and methods to recover useful components from scrap tires.

[0011] It would be desirable to provide additional methods for producing furfural that address at least one of the above-mentioned problems. It would also be desirable to provide methods for producing furfural that allow for high conversion of biomass components and / or high selectivity of furfural.

[0012] It is further desirable to find methods that allow for efficient recovery of valuable materials from scrap materials such as tire char. Summary of the Invention

[0013] The inventors of the present invention have found that solid zinc sulfate-rich catalysts have a strong catalytic effect on the production of furfural from a wide variety of biomass components by flash pyrolysis. Both purified zinc sulfate and transition metal doped zinc sulfate catalysts have been found to be effective in the above process. The inventors of the present invention have also discovered new methods for obtaining zinc sulfate and transition metal doped zinc sulfate, such as methods that provide catalysts useful in the production of furfural from scrap tire char.

[0014] Thus, in a first aspect, there is provided a method for producing furfural comprising the steps of pyrolyzing lignocellulosic material or a fraction thereof and producing furfural, wherein the production of said furfural is catalyzed by a solid zinc sulfate rich catalyst.

[0015] In some embodiments, the catalyst comprises at least 50% by weight zinc sulfate.

[0016] In some embodiments, the solid zinc sulfate rich catalyst contains an additional transition metal. In some embodiments, the additional transition metal is palladium, iron, copper, cobalt, or nickel. In some embodiments, the additional transition metal is palladium.

[0017] In some embodiments, the solid zinc sulfate rich catalyst contains palladium metal and / or palladium oxide.

[0018] In a further embodiment, the solid zinc sulfate rich catalyst contains 0.2 to 5 wt. % of an additional transition metal.

[0019] In some embodiments, the solid zinc sulfate rich catalyst contains 1 to 5 wt. % of an additional transition metal.

[0020] In some embodiments, the catalyst consists essentially of zinc sulfate.

[0021] In some embodiments, the lignocellulosic material or fraction thereof is selected from the group consisting of wood chips, sawdust, sugar cane, corn cobs, bagasse, oat hulls, cottonseed hulls, rice hulls, and wheat bran.

[0022] In further embodiments, the lignocellulosic material or fraction thereof is selected from the group consisting of a cellulose fraction and a hemicellulose fraction.

[0023] In further embodiments, the lignocellulosic material or fraction thereof is selected from the group consisting of monosaccharides, disaccharides and oligosaccharides.

[0024] In some embodiments, the lignocellulosic material or fraction thereof is selected from the group consisting of allose, glucose and xylan.

[0025] In some embodiments, prior to pyrolysis, the lignocellulosic material or fraction thereof is subjected to one or more pre-processing steps to either remove lignin fractions and / or hydrolyze sugar bonds.

[0026] In some embodiments, the production of furfural is carried out in the absence of steam.

[0027] In some embodiments, the production of furfural is carried out in the presence of steam.

[0028] In preferred embodiments, the weight ratio of steam to the lignocellulosic material or fraction thereof is within the range of about 0.1:1 to about 20:1, in some cases about 8:1 to about 20:1.

[0029] In some embodiments, the pyrolysis and / or production of furfural is carried out at a temperature in the range of about 300 to about 500°C.

[0030] In some embodiments, the method according to the present invention is carried out as a batch process.

[0031] In some embodiments, methods according to the present invention are carried out as a continuous or semi-continuous process.

[0032] In some embodiments, methods according to the present invention include a step of separating the furfural from other reaction products.

[0033] In a further embodiment, the furfural is separated by distillation.

[0034] In a further embodiment, furfural is separated by selective condensation of a product vapor stream containing furfural.

[0035] In another aspect, there is also provided furfural produced by the processes defined herein.

[0036] In another aspect, there is provided a method for producing one or more of furfuryl alcohol, furoic acid, furan, tetrahydrofuran, levulinic acid, butadiene, hexamethylenediamine, tetrahydrofurfuryl alcohol, methyltetrahydrofuran, and furfural phenolic resin, comprising producing furfural according to a method according to the invention and converting the furfural to furfuryl alcohol, furoic acid, furan, tetrahydrofuran, levulinic acid, butadiene, hexamethylenediamine, tetrahydrofurfuryl alcohol, methyltetrahydrofuran, and furfural phenolic resin.

[0037] In another aspect, a method for producing solid zinc sulfate is provided that includes contacting tire char with an aqueous sulfuric acid solution and producing a mixture of aqueous zinc sulfate and solid tire char residue, separating the aqueous zinc sulfate solution from the solid tire char residue, and recovering the solid zinc sulfate from the aqueous zinc sulfate solution.

[0038] In a preferred embodiment, the step of contacting the tire char with the aqueous sulfuric acid solution is carried out at a temperature within the range of about 25 to about 90°C.

[0039] In some embodiments, the aqueous sulfuric acid has a sulfuric acid concentration in the range of about 1 to about 5 moles per liter and is used in a weight ratio of aqueous sulfuric acid to tire char in the range of 1.5:1 to 10:1.

[0040] In some embodiments, the aqueous zinc sulfate solution is separated from the solid tire char residue by filtration.

[0041] In some embodiments, the solid zinc sulfate is recovered by one or more of evaporation, crystallization, and precipitation.

[0042] In some embodiments, the solid zinc sulfate is recovered from the aqueous sulfate solution by evaporation of water at a temperature in the range of 50 to 100° C. to reduce the water content, and subsequent precipitation of solid zinc sulfate.

[0043] In some embodiments, the reduction in water content during evaporation is controlled such that subsequent precipitation produces solid zinc sulfate heptahydrate.

[0044] In some embodiments, the method includes calcining solid zinc sulfate.

[0045] In some embodiments, the calcination step is carried out at a temperature in the range of about 400 to about 800°C.

[0046] In another aspect, a method is provided for producing transition metal doped zinc sulfate, comprising contacting tire char with an aqueous sulfuric acid solution and producing a mixture of aqueous zinc sulfate and solid tire char residue, separating the aqueous zinc sulfate solution from the solid tire char residue, recovering solid zinc sulfate from the aqueous zinc sulfate solution, contacting the zinc sulfate with an additional salt of a transition metal, and producing solid transition metal doped zinc sulfate.

[0047] In some embodiments, the additional transition metal is palladium, iron, cobalt, or nickel.

[0048] In some embodiments, the solid zinc sulfate is recovered from the aqueous zinc sulfate solution prior to contacting with additional transition metal salt.

[0049] In some embodiments, the solid zinc sulfate is mixed with an additional salt of a transition metal in the presence of an organic solvent, hi some embodiments, the organic solvent is ethanol.

[0050] In some embodiments, the solid zinc sulfate is mixed with an additional transition metal salt using sonication.

[0051] In some embodiments, the solid zinc sulfate is mixed with a salt of an additional transition metal present in a solvent-soluble form so as to impregnate the zinc sulfate with the additional transition metal.

[0052] In some embodiments, the organic solvent is removed by heating and / or vacuum drying.

[0053] In some embodiments, a salt of an additional transition metal is condensed on the surface of the solid zinc sulfate after it has been vaporized.

[0054] In some embodiments, a salt of an additional transition metal is mixed with the aqueous zinc sulfate solution and solid transition metal-doped zinc sulfate is produced by co-precipitation and / or co-crystallization.

[0055] In some embodiments, stabilizing metal salts and / or acidity adjusting metal salts are added.

[0056] In some embodiments, the stabilizing metal salt and / or acidity adjusting metal salt are mixed with an aqueous zinc sulfate solution and mixed with an additional salt of a transition metal, and solid transition metal doped zinc sulfate is produced by co-precipitation and / or co-crystallization.

[0057] In some embodiments, the method further comprises calcining the transition metal doped solid zinc sulfate, hi some embodiments, the calcining step is carried out at a temperature in the range of about 400 to about 800° C.

[0058] In some embodiments, the transition metal doped solid zinc sulfate is subjected to a reduction step after calcination by exposure to hydrogen at a temperature in the range of about 400 to about 800°C.

[0059] Further provided is the use of zinc sulfate produced according to the methods defined herein, or the use of transition metal doped zinc sulfate produced according to the methods defined herein, as a catalyst for producing furfural from lignocellulosic material or fractions thereof.

[0060] In another aspect, a method is provided for regenerating an active transition metal doped zinc sulfate catalyst used for producing furfural from lignocellulosic material or fractions thereof, comprising subjecting the transition metal doped zinc sulfate to a reduction step by exposure to hydrogen at a temperature in the range of about 400 to about 800° C.

[0061] In another aspect there is provided solid zinc sulfate when produced according to the processes defined herein.

[0062] In another embodiment, there is provided a transition metal doped solid zinc sulfate, wherein said transition metal is selected from the group consisting of palladium, iron, nickel and cobalt.

[0063] In some embodiments, the transition metal doped solid zinc sulfate contains at least 50% zinc sulfate by weight.

[0064] In some embodiments, the transition metal of the transition metal-doped solid is palladium, hi further embodiments, the transition metal-doped solid contains palladium metal and palladium oxide.

[0065] In some embodiments, the transition metal doped solid zinc sulfate contains 1 to 5 wt. % transition metal.

[0066] In some embodiments, the transition metal doped solid zinc sulfate contains additional stabilizing and / or acidity adjusting metals.

[0067] In another aspect, there is provided a transition metal doped zinc sulfate produced according to the methods defined herein. [Brief description of the drawings]

[0068] [Figure 1] 1 is a graph showing the selectivity of various products obtained from the pyrolysis of D-allose using various catalysts at 400° C. (a) and the conversion of D-allose. [Diagram 2] 1 is a graph showing the selectivity to various products obtained from the pyrolysis of D-allose and the conversion of D-allose (a) without and (b) with ZnSO4 / PdO catalyst at various temperatures. [Diagram 3]1 is a graph showing (a) the selectivity of various products obtained from the pyrolysis of D-allose, and (b) the conversion of D-allose, at various mass ratios of catalyst to allose at 400° C. [Figure 4] FIG. 1 is a graph showing (a) the selectivity of various products obtained from pyrolysis of D-allose, and (b) the conversion of D-allose, at various mass ratios of water to allose using 8x ZnSO4 / PdO as catalyst at 400° C. [Diagram 5] FIG. 1 is a graph showing (a) the selectivity of different products obtained from pyrolysis of D-glucose using different catalysts at 400° C., and (b) the conversion of D-glucose at different mass ratios of catalyst to glucose. [Figure 6] FIG. 1 shows DTG analysis of D-glucose (a) and D-allose (b) with and without catalyst when the mass ratio of catalyst to glucose or allose is 2. [Figure 7] 1 is a graph showing the selectivity to various products obtained from the pyrolysis of xylan using various catalysts (mass ratio of catalyst to xylan: 4) at 400° C., and the conversion of xylan. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0069] Throughout the description and claims of this specification, the word "comprise" and other forms of that word, such as "comprising" and "comprises," mean "including," but are not limited to, and are not intended to exclude, for example, other additives, components, integers, or steps.

[0070] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a composition" includes a mixture of two or more such compositions, reference to "the compound" includes a mixture of two or more such compounds, reference to "a metal" includes a mixture of two or more such metals, etc.

[0071] This disclosure refers to the entire contents of certain documents incorporated herein by reference. In the event of any conflicting teachings between the teachings of this disclosure and those documents, the teachings of this disclosure shall control.

[0072] Method for producing furfural In a first aspect, the present disclosure relates to a method for producing furfural, comprising pyrolyzing a lignocellulosic material or a fraction thereof and producing furfural, wherein the production of furfural is catalyzed by a solid zinc sulfate-rich catalyst.

[0073] The inventors have found that improved furfural selectivity and / or yield is observed when zinc sulfate-rich catalysts are used. The process according to the invention can be carried out with short residence times, allowing for high throughput. Furthermore, the process according to the invention utilizing zinc sulfate-rich catalysts can reduce wastewater production and can result in reduced corrosion to process equipment.

[0074] Furfural is an important industrial chemical that can be derived from biomass and used as a biobased starting substrate for the production of a variety of high value-added chemicals. Furfural has the chemical structure

[0075] [ka] It is also known as furan-2-carbaldehyde, furan-2-carboxaldehyde, fural, and 2-furaldehyde. Furfural is not only an important chemical in itself, but can also be converted, for example, into liquid hydrocarbon fuels, into derivative monomers for plastics, or into food additives and pharmaceuticals. Specific examples of downstream chemicals that can be produced using furfural include furfuryl alcohol, furoic acid, furan, tetrahydrofuran, levulinic acid, butadiene, hexamethylenediamine, tetrahydrofurfuryl alcohol, methyltetrahydrofuran, and furfural phenolic resins.

[0076] The method involves the use of lignocellulosic material or a fraction thereof as a feedstock. The lignocellulosic material contains cellulose, hemicellulose and / or lignin. In some embodiments, the lignocellulosic material used in the method is selected from the group consisting of wood chips, sawdust, sugar cane, corn cobs, bagasse, oat hulls, cottonseed hulls, rice hulls and wheat bran. In some embodiments, the lignocellulosic material used in the method is sugar cane. In some embodiments, the lignocellulosic material used in the method is bagasse. In some embodiments, the lignocellulosic material used in the method is corn cobs.

[0077] If desired, a fraction of lignocellulosic material can be used rather than crude lignocellulosic material. In some embodiments, a cellulose fraction is used (e.g., a fraction containing at least 50%, 60%, 70%, 80%, 90%, or at least 95% by weight of cellulose material), e.g., cellulose. In some embodiments, a hemicellulose fraction is used (e.g., a fraction containing at least 50%, 60%, 70%, 80%, 90%, or at least 95% by weight of hemicellulose material), e.g., hemicellulose. In some embodiments, a fraction low in lignin material (e.g., containing less than 10%, 5%, or 2% by weight of lignin material) or no lignin material is used.

[0078] The raw materials for the furfural production process include monosaccharides, disaccharides, oligosaccharides, polysaccharides, and mixtures thereof. In some embodiments, a lignocellulosic fraction selected from the group consisting of monosaccharides, disaccharides, oligosaccharides, and polysaccharides is used.

[0079] In some embodiments, monosaccharides are used or a mixture of monosaccharides. In some embodiments, disaccharides are used or a mixture of disaccharides or a mixture of monosaccharides and disaccharides. In some embodiments, oligosaccharides are used or a mixture of oligosaccharides or a mixture of oligosaccharides and monosaccharides or a mixture of oligosaccharides and disaccharides or a mixture of oligosaccharides, monosaccharides and disaccharides are used. In some embodiments, polysaccharides are used or a mixture of polysaccharides or a mixture of polysaccharides and monosaccharides or a mixture of polysaccharides and disaccharides or a mixture of polysaccharides and oligosaccharides or a mixture of polysaccharides, oligosaccharides and monosaccharides and / or disaccharides are used.

[0080] In some embodiments, monosaccharide-rich fractions (e.g., fractions that contain at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, or at least 95% by weight of monosaccharides), or disaccharide-rich fractions (e.g., fractions that contain at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, or at least 95% by weight of disaccharides), or oligosaccharide-rich fractions (e.g., fractions that contain at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, or at least 95% by weight of oligosaccharides) can be used.

[0081] Specific examples of monosaccharides suitable for use in the method according to the invention include allose, glucose, xylose, arabinose, mannose, fructose and galactose. In some embodiments, the feedstock used in the method is a monosaccharide or a monosaccharide-rich fraction, the monosaccharide being selected from the group consisting of allose, glucose, xylose, arabinose, mannose, fructose and galactose. In some embodiments, the feedstock is allose or an allose-rich fraction (e.g., containing at least 50% by weight of allose). In some embodiments, the feedstock is glucose or a glucose-rich fraction (e.g., containing at least 50% by weight of glucose).

[0082] Particular examples of disaccharides suitable for use in the method according to the invention include sucrose, lactose and maltose. In some embodiments, the feedstock used in the method is a disaccharide or a disaccharide-rich fraction, wherein the disaccharide is selected from the group consisting of sucrose, lactose and maltose.

[0083] In some embodiments, oligosaccharides are used. In some embodiments, polysaccharides are used. Specific examples of oligosaccharides and / or polysaccharides include xylan, mannan, araban, fructan and cellulose. In some embodiments, the fraction of the lignocellulosic material used is xylan. In some embodiments, the fraction of the lignocellulosic material used is cellulose.

[0084] Where a lignocellulosic fraction is used, the fraction may be obtained from the lignocellulosic material by any suitable process step or steps, which may be carried out as part of the method if desired, or may be pre-treated or pre-processed separately from the method, for example using a lignocellulosic fraction obtained from a supplier.

[0085] In methods that include a pre-processing step, such steps may, for example, involve one or more of the following: separation of the cellulose, hemicellulose and / or lignin fraction from one or more other fractions of the lignocellulosic material; (e.g., hydrolysis of sugar bonds present in polysaccharides and / or oligosaccharides; and separation of monosaccharide and / or disaccharide and / or oligosaccharide and / or polysaccharide fractions.

[0086] For example, lignocellulosic material may be exposed to high temperatures and / or pressures, and / or may be subjected to enzymatic hydrolysis, and / or may be subjected to acidic and / or alkaline conditions to produce mono-, di-, and / or oligosaccharides.

[0087] In some embodiments, the wood may undergo one or more pre-processing steps to remove lignin fractions and / or hydrolyze sugar bonds. This can be achieved by physical pre-treatment, such as crushing by grinding, chemical pre-treatment, such as using acidic or alkaline solutions and solvents, or biological pre-treatment, such as using microorganisms, including bacteria, and / or through enzymatic saccharification. For example, if wood chips are used as the feedstock, one or more pre-processing steps may be performed to improve the retrieval of the cellulose content and thereby the final yield of furfural.

[0088] If desired, the fraction of interest may be separated from other components to provide a feedstock enriched for the material of interest. Examples of suitable techniques include aqueous / organic extraction, precipitation / crystallization of the material from solution, and separation of solid / liquid fractions (e.g., filtration, decanting).

[0089] In situations where it is desired to remove the lignin fraction from the solid lignocellulosic material prior to use in the above methods, in some embodiments pre-processing includes treating the lignocellulosic material with an aqueous alkaline solution at elevated temperatures to solubilize the lignin and separating the solid and liquid components.

[0090] The process for producing furfural involves pyrolyzing lignocellulosic material or a fraction thereof, which is the thermal decomposition of the material using high temperatures, typically carried out in the presence of nitrogen or argon.

[0091] Pyrolysis of the lignocellulosic material or fractions thereof can be carried out at any suitable temperature, for example, at a temperature in the range of about 200 to about 600° C. In some embodiments, the pyrolysis step is carried out at a temperature range of about 300 to about 500° C., or about 300 to about 400° C., or about 350 to about 450° C., or about 400 to about 500° C. In some embodiments, the pyrolysis step is carried out at a temperature of about 300° C., about 350° C., about 400° C., about 450° C., or about 500° C.

[0092] The pyrolysis step is carried out for a suitable time to effectively pyrolyze the lignocellulosic material or fraction thereof. For example, the pyrolysis step has a time (e.g., a holding time or residence time of the pyrolysis reaction) in the range of about 5 seconds to about 2 minutes, or about 10 seconds to about 60 seconds, or about 20 seconds to about 50 seconds. In some embodiments, the time of the pyrolysis step (the holding time) is in the range of about 25 seconds to 45 seconds. In some embodiments, the time of the pyrolysis step is about 10 seconds, about 15 seconds, about 20 seconds, about 25 seconds, about 30 seconds, about 35 seconds, about 40 seconds, about 45 seconds, about 50 seconds, about 55 seconds, or about 60 seconds.

[0093] Any suitable pyrolysis reactor can be used to carry out the pyrolysis step, for example a fluidized bed reactor, hi some embodiments, a fluidized bed reactor is used.

[0094] The present inventors have discovered that the use of solid zinc sulfate rich catalysts exhibits high catalytic activity resulting in high conversion and selectivity in the production of furfural when used in the catalytic pyrolysis of lignocellulosic materials.

[0095] As defined herein, the term "zinc sulfate rich" refers to a material that contains at least 20% zinc sulfate by weight. In some embodiments, the zinc sulfate rich material (e.g., zinc sulfate rich catalyst) comprises at least 30% zinc sulfate by weight, at least 40% by weight, at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or at least 95% zinc sulfate by weight, or at least 98% zinc sulfate by weight, or at least 99% zinc sulfate by weight. In some embodiments, the catalyst consists essentially of zinc sulfate or consists of zinc sulfate.

[0096] In some embodiments, the zinc sulfate may be present in anhydrous or hydrated form. For example, in some embodiments, the zinc sulfate may be zinc sulfate heptahydrate. In some other embodiments, the zinc sulfate may be anhydrous zinc sulfate. References to wt% zinc sulfate in this disclosure refer to the wt% of the form of zinc sulfate used. For example, if zinc sulfate heptahydrate is used, the term "wt% zinc sulfate" refers to the wt% of zinc sulfate heptahydrate present in the material (e.g., present in a zinc sulfate rich catalyst).

[0097] Any suitable amount of solid zinc sulfate rich catalyst may be used in the method. In some embodiments, the weight ratio of catalyst to lignocellulosic material is in the range of 1:1 to 20:1, such as 2:1 to 15:1, or in the range of about 6:1 to 10:1. In some embodiments, the weight ratio of catalyst to feedstock is about 1:1, about 2:1, about 3:1, about 4:1, about 5:1, about 6:1, about 7:1, about 8:1, about 9:1, about 10:1, about 11:1, about 12:1, about 13:1, about 14:1, or about 15:1.

[0098] Various forms of the solid zinc sulfate rich catalyst can be used in the above process. For example, transition metal doped or undoped forms of the catalyst can provide particularly advantageous results depending on the lignocellulosic material used as a feedstock. While in some embodiments, pure zinc sulfate or substantially pure zinc sulfate can be used, in some other embodiments, the solid zinc sulfate rich catalyst contains an additional transition metal. Reference to an additional transition metal is understood to be a transition metal other than zinc.

[0099] As demonstrated by the examples, doping of zinc sulfate with a transition metal such as palladium can provide desirable properties when used in methods according to the present disclosure. In some embodiments, the additional transition metal is selected from the group consisting of palladium, iron, copper, cobalt, and nickel. In some embodiments, the additional transition metal is palladium or iron. In some embodiments, the additional transition metal is palladium.

[0100] Without being bound to any particular theory, it is believed that the incorporation of a transition metal such as palladium improves the conversion, and subsequent yield, of furfural from the feedstock by assisting in the cleavage of C-C bonds present in C6 sugars.

[0101] Thus, in some embodiments, a solid zinc sulfate-rich catalyst doped with an additional transition metal (e.g., palladium) is used, and the lignocellulosic material or fraction thereof used in the method is enriched in C6 sugars (e.g., C6 monosaccharides, C6 disaccharides, C6 oligosaccharides, and / or C6 polysaccharides). A lignocellulosic material or fraction enriched in C6 sugars is one that contains at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, or at least 95% by weight of C6 sugars.

[0102] It has also been found that for feedstocks rich in C5 sugars, such as xylans, solid zinc sulfate catalysts not doped with additional transition metals work particularly well in the process. Thus, in some embodiments, a solid zinc sulfate rich catalyst not doped with additional transition metals is used, so that the lignocellulosic material or fraction used in the process is rich in C5 sugars (e.g., C5 monosaccharides, C5 disaccharides, C5 oligosaccharides, and / or C5 polysaccharides). A lignocellulosic material or fraction rich in C5 sugars is one that contains at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or at least 95% by weight of C5 sugars.

[0103] When the solid zinc sulfate rich catalyst is doped with an additional transition metal, the additional transition metal is typically present in an amount of up to 20% by weight. In some embodiments, the transition metal is present in an amount of about 0.1 to about 10% by weight, or about 1 to about 5% by weight, based on the total weight of the catalyst. In some embodiments, the transition metal is present in an amount of about 0.5%, about 1%, about 1.5%, about 2%, about 2.5%, about 3%, about 3.5%, about 4%, about 4.5%, or about 5% by weight.

[0104] In some embodiments, the solid zinc sulfate rich catalyst contains about 0.1 to about 5 wt.% additional transition metal, such as 0.2 to 5 wt.%, or 0.5 to 3 wt.%, or about 0.2 wt.%, about 0.5 wt.%, about 1 wt.%, about 2 wt.%, about 3 wt.%, about 4 wt.%, or about 5 wt.% additional transition metal.

[0105] If the solid zinc sulfate-rich catalyst is doped with a further transition metal, said further transition metal may for example be mixed or co-precipitated with the solid zinc sulfate-rich catalyst, or the surface (or at least a part of the surface) of the solid zinc sulfate-rich catalyst may be coated with the further transition metal.

[0106] Any suitable form of the additional transition metal can be used with the solid zinc sulfate rich catalyst. For example, a salt form of the additional transition metal can be used. The additional transition metal can also or alternatively be present as an oxide. The additional transition metal can also or alternatively be present in the form of the metal itself. In some embodiments, the additional transition metal can be present in the form of a mixture, for example as an oxide, and as the metal itself. For example, in some embodiments, the additional transition metal present on the surface of the solid zinc sulfate rich catalyst can be present mainly as an oxide, and the additional transition metal present in the interior of the zinc sulfate rich catalyst can be present mainly as the metal. In the case of palladium, for example, in some embodiments, palladium can be present in the solid zinc sulfate rich catalyst as palladium metal and / or palladium oxide.

[0107] When the additional transition metal is added using a salt form of the additional transition metal, representative salts include nitrates, sulfates, acetates, chlorides, bromides and iodides. In some embodiments, the additional transition metal is added using a nitrate of the transition metal. In some embodiments, the additional transition metal is palladium, and palladium nitrate is added to solid zinc sulfate.

[0108] In some embodiments, the transition metal doped solid zinc sulfate rich catalyst contains additional stabilizing and / or acidity adjusting metals.

[0109] The catalyst may, if desired, be subjected to additional processing steps prior to use, for example the catalyst may be subjected to granulation to produce catalyst granules.

[0110] The method may be carried out using any suitable apparatus or reactor system. In some embodiments, the method is carried out as a batch process. In some other embodiments, the method is carried out as a continuous or semi-continuous process.

[0111] The pyrolysis of the lignocellulosic material or a fraction thereof and the production of furfural catalyzed by a solid zinc sulfate-rich catalyst may be carried out as a single step in a single reactor in some embodiments. However, in other embodiments, the pyrolysis of the lignocellulosic material or a fraction thereof and the production of furfural catalyzed by a solid zinc sulfate-rich catalyst may be carried out as separate steps. For example, pyrolysis may be carried out to generate a lignocellulosic vapor stream (e.g., in a first reactor), and the lignocellulosic vapor stream may be contacted with a solid zinc sulfate-rich catalyst to produce furfural (e.g., in a second reactor). For example, the lignocellulosic vapor stream may pass over and / or through a bed of the solid zinc sulfate-rich catalyst. In some embodiments, the furfural production step is carried out using a fluidized bed reactor or using a packed bed reactor. For example, a reactor containing a granulated catalyst (e.g., a fluidized bed reactor or a packed bed reactor) may be used.

[0112] In some embodiments, pyrolysis and contact with a catalyst are carried out as separate steps, where in a first step (e.g., in a fluidized bed reactor) the lignocellulosic material or a fraction thereof is pyrolyzed to produce a lignocellulosic vapor stream, which is then transported, together with introduced steam if desired, to a second reactor (e.g., a packed bed reactor or a moving bed reactor) containing granulated catalyst by a stream containing argon and / or nitrogen, and then the lignocellulosic vapor stream is contacted with a catalyst to produce furfural, and finally a product vapor stream containing furfural is obtained.

[0113] The production of furfural can be carried out at any suitable temperature, for example, at a temperature within the range of about 200 to about 600° C. In some embodiments, the production of furfural is carried out at a temperature range of about 300 to about 500° C., or about 300 to about 400° C., or about 350 to about 450° C., or about 400 to about 500° C. In some embodiments, the production of furfural is carried out at a temperature of about 300° C., about 350° C., about 400° C., about 450° C., or about 500° C.

[0114] The production of furfural by contacting with a solid zinc sulfate-rich catalyst is carried out for a suitable time to provide high conversion to furfural. For example, the catalyst contacting step may be carried out for a period of time within the range of about 5 seconds to about 2 minutes, or about 10 seconds to about 60 seconds, or about 20 seconds to about 50 seconds. In some embodiments, the solid zinc sulfate-rich catalyst contacting step may be carried out for a period of time within the range of about 25 seconds to 45 seconds. In some embodiments, the period of time is about 10 seconds, about 15 seconds, about 20 seconds, about 25 seconds, about 30 seconds, about 35 seconds, about 40 seconds, about 45 seconds, about 50 seconds, about 55 seconds, or about 60 seconds.

[0115] When pyrolysis and production of furfural are carried out as part of a single step, the temperatures and time periods listed above, for example, are applicable to that single step.

[0116] The inventors have found that the presence or absence of water vapor / steam can affect the final yield of furfural. In some embodiments, the method for producing furfural is carried out in the absence of steam, for example, when the production of furfural is carried out under a nitrogen or argon atmosphere. In some other embodiments, the production of furfural is carried out in the presence of steam, for example, when steam / water vapor is added to a nitrogen and / or argon atmosphere. In some embodiments, the weight ratio of steam to the lignocellulosic material or fraction thereof used is in the range of about 0.1:1 to about 30:1, or about 5:1 to about 30:1, or about 0.1:1 to about 20:1, or about 1:1 to about 20:1, or about 8:1 to about 20:1. In some embodiments, the weight ratio of steam to lignocellulosic material is about 0.1:1, about 0.5:1, about 1:1, about 2:1, about 3:1, about 4:1, 5:1, about 6:1, about 7:1, about 8:1, about 9:1, about 10:1, about 11:1, about 12:1, about 13:1, about 14:1, about 15:1, about 16:1, about 17:1 about 18:1, about 19:1, or about 20:1.

[0117] The reaction typically results in a furfural-containing product vapor stream that can be easily separated from the solid zinc sulfate-rich catalyst.

[0118] If desired, the product mixture containing furfural may be separated from other organic components. For example, since a certain amount of by-products such as light compounds (LC, e.g., acetic acid and furan), levulinic acid (LA), 5-hydroxymethylfurfural (5-HMF) and levoglucosenone (LGO) may be produced, it may be desirable to separate furfural from those components or to reduce the concentration of those by-products. Any suitable processing technique may be used to separate and / or purify furfural.

[0119] In some embodiments, furfural is separated from other components by distillation, e.g., fractional distillation may be used, e.g., using a series of columns and appropriate temperature conditions to separate furfural from higher and / or lower boiling components of the product mixture as needed.

[0120] In some other embodiments, furfural is separated by selective condensation of a product vapor stream containing furfural. The product vapor stream containing furfural is at an elevated temperature. By appropriately adjusting (i.e., lowering) the temperature of the product stream, by-products having a higher boiling point than furfural can first be separated from the furfural remaining in the gas phase. Following the separation of the high boiling point materials, the temperature of the vapor stream containing furfural can then be lowered (e.g., below the boiling point of furfural) to condense the furfural, which can finally be separated from the by-products having a lower boiling point.

[0121] As discussed above, the present methods produce furfural. Accordingly, there is also provided furfural produced by the methods defined herein.

[0122] The method for producing furfural also provides access to downstream chemicals that may be produced from the furfural. Thus, in another aspect, there is provided a method for producing one or more of furfuryl alcohol, furoic acid, furan, tetrahydrofuran, levulinic acid, butadiene, hexamethylenediamine, tetrahydrofurfuryl alcohol, methyltetrahydrofuran, and furfural phenolic resin, comprising producing furfural according to a method according to the invention and converting the furfural to furfuryl alcohol, furoic acid, furan, tetrahydrofuran, levulinic acid, butadiene, hexamethylenediamine, tetrahydrofurfuryl alcohol, methyltetrahydrofuran, and furfural phenolic resin.

[0123] Methods for producing the above-mentioned reference compounds from furfural are known in the art.For example, furfuryl alcohol can be produced by, for example, hydrogenation and reduction using a suitable catalyst (such as nickel, palladium, platinum, or zinc-copper catalyst), electrocatalytic reduction, enzymatic reduction, or biotransformation using a suitable bacterium or yeast (see, for example, U.S. Pat. No. 2,077,409; Gutierrez et al., Appl. Biochem. Biotechnol., 2002, 98-100, 327-40; Brosnahan et al., Nanoscale, 2021, 13, 2312-2316, the entire contents of which are incorporated herein by reference).

[0124] Furan acids can be produced, for example, by oxidation of furfural, or furfuryl alcohol (e.g., with permanganate or dichromate). As a further example, the aqueous Cannizzaro reaction (e.g., treatment of furfural with an aqueous solution of an alkali such as sodium hydroxide) may be used to produce a mixture of furano acids (after acidification of the product mixture) and furfuryl alcohol.

[0125] Furans can be produced, for example, by decarbonylation of furfural (e.g., over palladium, zeolite, or nickel-magnesium oxide catalysts) or by decarboxylation of furoic acid (which itself can be produced from furfural). See, for example, Jiminez-Gomez et al, ACS Sustainable Chem. Eng., 2019, 7, 8, 7676-7685, WO 2015 / 020845, EP 3126342, and U.S. Pat. No. 7,044,480, the entire contents of which are incorporated herein by reference.

[0126] Tetrahydrofuran can be produced, for example, by hydrogenation of furan (which itself can be produced from furfural), for example using a palladium catalyst such as palladium oxide, or directly from furfural without isolating an intermediate product (for example by reduction using hydrogen and a palladium catalyst). See, for example, WO 2014 / 118806, the entire contents of which are incorporated herein by reference, and Org. Synth. 1936, 16, 77.

[0127] Levulinic acid can be produced, for example, by treatment with an alcohol (e.g., methanol) and a dialkoxymethane (e.g., dimethoxymethane) to produce an alkyl levulinate that can be hydrolyzed (e.g., under acidic aqueous conditions) to produce levulinic acid (see, e.g., Shao et al, Green Energy and Environment, 2019, 4, 4, 400-413, the entire contents of which are incorporated herein by reference).

[0128] Butadiene can be produced, for example, by converting furfural to tetrahydrofuran, and then converting tetrahydrofuran to butadiene, e.g., by dehydrative ring-opening (e.g., using a zeolite catalyst such as a silica-phosphorus zeolite (see, e.g., Abdelrahman et al, ACS Sustainable Chem. Eng., 2017, 5, 5, 3732-3736, the entire contents of which are incorporated herein by reference), as discussed above.

[0129] Hexamethylenediamine can be produced, for example, by conversion of furfural to 1,6-hexanediol, followed by amination to produce hexamethylenediamine (see, for example, U.S. Pat. No. 9,518,005, the entire contents of which are incorporated herein by reference).

[0130] Tetrahydrofurfuryl alcohol can be produced, for example, from furfuryl alcohol (which itself can be produced from furfural) or can be produced directly from furfural by hydrogenation in the presence of a suitable catalyst such as, for example, a hydroxyapatite-supported palladium catalyst (see, for example, Li et al., Ind. Eng. Chem. Res., 2017, 56, 31, 8843-8849, the entire contents of which are incorporated herein by reference).

[0131] 2-Methyltetrahydrofuran can be produced, for example, by reducing furfural, e.g., hydrogenating it in the presence of a suitable catalyst (e.g., reducing it in the presence of a Co-based catalyst to produce 2-methylfuran, or reducing it in the presence of a Ni-based catalyst to produce 2-methyltetrahydrofuran). See, for example, Liu et al, Molecular Catalysis, 2020, 490, 110951, the entire contents of which are incorporated herein by reference.

[0132] Furfural phenolic resins can be prepared, for example, by reacting phenol with furfural in the presence of a base, such as sodium hydroxide.

[0133] Method for producing solid zinc sulfate The disposal of rubber tires at the end of their life cycle presents a waste management challenge for many developing and developed countries. Improper disposal of waste or scrap tires can lead to many health, safety and environmental hazards. Pyrolysis of waste tires is a commonly used process for processing waste tires that involves exposure to high temperatures in an oxygen-poor atmosphere. Pyrolysis of waste tires typically provides a significant component of solid tire char, but the demand for the pyrolysis char is limited because it typically contains many contaminants. One use of the pyrolysis char is to convert it into activated carbon, but such processes often result in the leaching of metal ions into water, creating environmental hazards.

[0134] The inventors have discovered a method that allows for the production of zinc sulfate from waste sources such as tire char, for example facilitating the production of a solid zinc sulfate rich catalyst as described above. Thus, in another aspect, there is provided a method for producing solid zinc sulfate, comprising contacting tire char with an aqueous sulfuric acid solution and producing a mixture of aqueous zinc sulfate and solid tire char residue, separating the aqueous zinc sulfate solution from the solid tire char residue, and recovering the solid zinc sulfate from the aqueous zinc sulfate solution.

[0135] Utilizing this method allows zinc waste to be captured, isolated in solid form, and used in materials or downstream processes such as pyrolysis and conversion of lignocellulosic materials to furfural.

[0136] The method involves contacting the tire char with an aqueous solution of sulfuric acid. Typically, the aqueous solution of sulfuric acid and the tire char are mixed (e.g., the tire char can be added to the aqueous solution of sulfuric acid or vice versa) and then mixed for a suitable period of time to allow for leaching of zinc from the tire residue and the production of an aqueous solution of zinc sulfate. The mixture may be vigorously stirred or mixed, for example, using a mixer, to facilitate the reaction. In some embodiments, the mixing step of the tire char and the sulfuric acid is carried out under stirring controlled at a specific speed. If the mixture is stirred, the stirring speed may be, for example, within the range of about 100 rpm to about 600 rpm, or about 200 rpm to about 400 rpm, or at a speed of about 100 rpm, about 200 rpm, about 300 rpm, about 400 rpm, about 500 rpm, or about 600 rpm.

[0137] The step of contacting the tire char with the aqueous sulfuric acid solution is carried out at a temperature suitable to leach zinc from the tire char to produce an aqueous zinc sulfate solution. For example, the step can be carried out at a temperature within the range of about 25 to about 90° C., or about 40 to about 80° C., or at about 30° C., about 40° C., about 50° C., about 60° C., about 70° C., about 75° C., about 80° C., about 85° C., or about 90° C.

[0138] The concentration of sulfuric acid in the aqueous sulfuric acid solution is typically in the range of about 0.5 to about 15 moles per liter, for example, in some embodiments, in the range of about 1 to about 10 moles per liter, or about 1 to about 5 moles per liter. In some embodiments, the concentration of the aqueous sulfuric acid solution is about 1, about 2, about 3, about 4, or about 5 moles per liter.

[0139] The amount of aqueous sulfuric acid used is such that it facilitates the extraction of zinc from the tire char. The volume:mass ratio of aqueous sulfuric acid to tire char is typically within the range of about 1:1 to 20:1, or about 1:1 to 10:1, or about 1.5:1 to 10:1, or about 1:1 to 6:1, or about 1.5:1 to 6:1, or about 1:1 or about 2:1 or about 3:1, or about 4:1, or about 5:1, or about 6:1.

[0140] In some embodiments, the aqueous sulfuric acid has a sulfuric acid concentration in the range of about 1 to about 5 moles per liter and is used in a volume:mass ratio of aqueous sulfuric acid to tire char in the range of 1.5:1 to 10:1.

[0141] The step of contacting the tire char with the aqueous sulfuric acid solution is carried out for a suitable period of time to facilitate extraction of the zinc as zinc sulfate. In some embodiments, the contacting step is carried out for a period of time ranging from 5 minutes to 24 hours, e.g., from 5 minutes to 12 hours, or from 5 minutes to 6 hours, or from 10 minutes to 2 hours, or for about 10 minutes, about 20 minutes, about 30 minutes, about 40 minutes, about 50 minutes, about 1 hour, about 1.5 hours, or about 2 hours.

[0142] The step of contacting the tire char with the aqueous sulfuric acid solution can be carried out using any suitable equipment, for example, a continuous stirred tank reactor (CSTR).

[0143] If desired, the tire char may undergo one or more pre-processing steps prior to contacting with the aqueous sulfuric acid solution. For example, following pyrolysis of scrap tires, the tire char produced may, if desired, be ground and sieved to reduce particle size, for example to produce tire char having an average particle size within the range of 100 to 500 μm, or about 200 to 400 μm, or about 250 to 300 μm. It is understood that reducing particle size facilitates easier extraction of zinc. Steel and / or wire components may, for example, be removed from the tire char prior to contacting with the aqueous sulfuric acid solution. The tire char may, for example, be washed, for example with water or an aqueous solvent, prior to contacting with the aqueous sulfuric acid solution.

[0144] Thus, in some embodiments, prior to contacting with the aqueous sulfuric acid solution, the tire char is subjected to one or more of the following process steps: Particle size reduction (e.g., by grinding and / or sieving the tire char); Removal of steel and / or wire from tire char; and Washing with water or an aqueous solvent. It is attached to.

[0145] After contacting the tire char with this step, the aqueous zinc sulfate solution is separated from the solid tire char residue. Many methods can be used to separate the aqueous zinc sulfate solution from the solid tire char residue, such as by filtration, or by allowing the solids to settle and decanting, siphoning or otherwise recovering the liquid components. In some embodiments, the aqueous zinc sulfate solution is separated from the solid tire char residue by filtration. If desired, the solid tire char residue may be washed, for example, with water or an aqueous solvent to recover additional zinc sulfate.

[0146] Solid zinc sulfate is recovered from the aqueous zinc sulfate solution after a separation step from the tire char residue. Suitable processing techniques include recovering the solid zinc sulfate by one or more of evaporation, crystallization and precipitation.

[0147] In some embodiments, water is removed by one or more of evaporation and / or distillation. The aqueous zinc sulfate solution may, for example, be heated to a temperature in the range of 50 to 100° C., such as about 50° C., about 60° C., about 70° C., about 80° C., about 90° C., about 95° C., or about 100° C. For example, vacuum distillation may be used, which allows water to be removed at temperatures below atmospheric pressure.

[0148] For example, in some embodiments, water is evaporated from the aqueous zinc sulfate solution by boiling the mixture (e.g., heating to about 100° C.). In some other embodiments, the pressure may be reduced and water may be evaporated by heating at a temperature in the range of 50 to 60° C.

[0149] The effect of evaporation and / or distillation is to concentrate the aqueous zinc sulfate mixture. Typically, the amount of water is reduced such that a saturated solution of zinc sulfate is produced, and solid zinc sulfate crystallizes and / or precipitates out of solution.

[0150] Thus, in some embodiments, solid zinc sulfate is recovered by evaporation of water from an aqueous sulfate solution at a temperature in the range of 50 to 100° C. to reduce the water content, and subsequent precipitation and / or crystallization of solid zinc sulfate.

[0151] In some other embodiments, solid zinc sulfate may be obtained by addition of an anti-solvent, such as a water-miscible organic solvent, which ultimately precipitates and / or crystallizes solid zinc sulfate.

[0152] Any suitable equipment can be used to carry out the evaporation, distillation, precipitation and / or crystallization steps, for example a crystallizer, such as a Swenson DTE crystallizer, can be used to obtain solid zinc sulfate.

[0153] The resulting solid zinc sulfate can be separated from the water or aqueous solvent by any suitable method, for example by filtration or by allowing the solid components to settle and removing the liquid fraction, for example by siphoning or decanting.

[0154] In some embodiments, the remaining liquid components may be subjected to further processing steps to recover additional zinc sulfate from the solution. For example, in some embodiments, the resulting solution may be subjected to one or more evaporation-precipitation cycles.

[0155] In some embodiments, zinc sulfate is recovered from the aqueous zinc sulfate solution in the form of zinc sulfate heptahydrate.

[0156] Thus, in some embodiments, an evaporation or distillation step is performed to remove water and concentrate the zinc sulfate in solution to a concentration such that subsequent crystallization and / or precipitation produces zinc sulfate heptahydrate. In some embodiments, the reduction in the amount of water during evaporation is controlled such that subsequent precipitation produces solid zinc sulfate heptahydrate. In some embodiments, solid zinc sulfate is recovered by crystallization from water or an aqueous solvent, and the amount of water used is controlled such that crystallization produces solid zinc sulfate heptahydrate.

[0157] The evaporation step can be controlled under certain conditions such that a subsequent precipitation step produces solid zinc sulfate heptahydrate. For example, the aqueous zinc sulfate mixture can be first heated to about 100° C. to remove water to produce a saturated solution of zinc sulfate, and then heated at a lower temperature (e.g., in the range of 50 to 60° C.) while reducing the pressure with additional water removal to produce zinc sulfate heptahydrate.

[0158] Depending on the intended use of the recovered solid zinc sulfate, it may then be subjected to a calcination step, for example to remove impurities. Thus, in some embodiments, the method includes a step of calcining the solid zinc sulfate.

[0159] Calcination refers to the process of heating a solid to an elevated temperature in the absence of air or oxygen. Any suitable equipment that allows for controlled calcination conditions can be used, for example a reactor such as a packed bed reactor.

[0160] The calcination step is carried out at an elevated temperature, for example, in the range of about 300 to about 1000° C. In some embodiments, the calcination step is carried out at a temperature in the range of about 400 to about 800° C., for example, about 400° C., about 500° C., about 600° C., about 700° C., or about 800° C.

[0161] The calcination step may be carried out in the presence of an inert atmosphere such as, for example, argon or nitrogen.

[0162] Upon recovery of zinc from scrap tire char, the resulting tire char can then be used as a clean fuel in power plants or can be further upgraded using conventional processes to advanced sorbents such as carbon black. Thus, in some embodiments, the method includes recovering a solid tire char residue. In some embodiments, the method includes recovering a solid tire char residue and converting the solid tire char residue to carbon black.

[0163] Method for producing transition metal doped zinc sulfate Also provided herein are methods for producing transition metal doped zinc sulfate (i.e., zinc sulfate doped with a transition metal other than zinc), such materials being used, for example, as catalysts for producing furfural, as discussed herein.

[0164] The method includes contacting tire char with an aqueous sulfuric acid solution and producing a mixture of aqueous zinc sulfate and solid tire char residue, separating the aqueous zinc sulfate solution from the solid tire char residue, recovering solid zinc sulfate from the aqueous zinc sulfate solution, contacting the zinc sulfate with an additional salt of a transition metal, and producing solid transition metal doped zinc sulfate.

[0165] The steps of contacting the tire char with the aqueous sulfuric acid solution, separating the aqueous zinc sulfate solution from the solid tire char residue, and recovering solid zinc sulfate from the aqueous zinc sulfate solution can be carried out as described above in the context of the discussion of the methods for producing solid zinc sulfate, and the embodiments discussed with respect to those methods also apply to the methods for producing transition metal doped zinc sulfate.

[0166] The transition metal doped into zinc sulfate may be any desired transition metal other than zinc. In the case of zinc sulfate doped with a transition metal intended for use as a catalyst for producing furfural, the transition metal may be, for example, one that enhances catalytic activity, and may be, for example, one selected from the group consisting of palladium, iron, cobalt, and nickel. In some embodiments, the transition metal is palladium or iron. In some embodiments, the transition metal is palladium.

[0167] The transition metal doped solid zinc sulfate can be prepared by several means.

[0168] In some embodiments, solid zinc sulfate is recovered from the aqueous zinc sulfate solution prior to the step of contacting with a salt of a transition metal.

[0169] When the transition metal is added using a salt form of the transition metal, representative salts include nitrates, sulfates, acetates, chlorides, bromides and iodides. In some embodiments, the transition metal is added using a nitrate of the transition metal. In some embodiments, the transition metal is palladium and palladium nitrate is added to solid zinc sulfate.

[0170] In embodiments where the salt form of the transition metal is contacted with solid zinc sulfate, this can be done, for example, by mixing the solid zinc sulfate with the transition metal salt in the presence of an organic solvent. Any organic solvent that solubilizes the transition metal salt can be used, for example, an alcoholic solvent can be used. In some embodiments, the organic solvent is ethanol.

[0171] Typically, solid zinc sulfate and transition metal salt solutions are combined in suitable amounts, in some embodiments, the liquid to solid ratio is 10 mL / g.

[0172] The solution containing the transition metal salt and the solid zinc sulfate is usually mixed for a suitable period of time to ensure good mixing of the components and the formation of a homogeneous mixture. The mixing step can be accomplished using any suitable technique, for example, an overhead stirrer can be used. In some embodiments, the solid zinc sulfate is mixed with the additional transition metal salt using ultrasonic treatment. Ultrasonic treatment is the use of sound energy at ultrasonic frequencies to vigorously agitate and mix particles in the solution. The ultrasonic treatment step may be carried out for a suitable period of time. In some embodiments, the solution containing the solid zinc sulfate catalyst and the additional transition metal salt is subjected to ultrasonic treatment for a period of time ranging from about 5 minutes to 1 hour, or from about 10 to about 30 minutes.

[0173] In some embodiments, the solid zinc sulfate is mixed with a salt of an additional transition metal present in a solvent-soluble form so as to impregnate the zinc sulfate with the additional transition metal.

[0174] The step of mixing the solid zinc sulfate with the additional transition metal salt can be carried out using any suitable equipment, for example, a continuous stirred tank reactor (CSTR) can be used.

[0175] If the transition metal is introduced by an organic solvent solution, after the mixing step, the organic solvent may usually be removed. This may be accomplished, for example, by a heating and / or vacuum drying step to remove the organic solvent. For example, the mixture may be heated in an oven or autoclave at a temperature within the range of, for example, about 50° C. to about 250° C., or about 150° C. to about 250° C., or about 160° C. to about 200° C., or about 150° C., or about 160° C., or about 170° C., or about 180° C., or about 190° C., or about 200° C., or about 210° C., or about 220° C., or about 230° C., or about 240° C., or about 250° C. Suitable periods of time for removal of the organic solvent at elevated temperatures may be, for example, within the range of 3 to 24 hours, or 6 to 24 hours, or 12 to 16 hours, or about 6, about 8, about 10, about 12, about 14, or about 16 hours. In some embodiments, the organic solvent is removed by hydrothermal treatment in an autoclave at a temperature in the range of 150° C. to about 250° C. and for a period in the range of 12 hours to about 16 hours.

[0176] In some embodiments, when solid zinc sulfate is recovered from the aqueous zinc sulfate solution prior to the step of contacting with the transition metal salt, the transition metal-doped solid zinc sulfate is produced by condensing transition metal vapor onto the surface of the solid zinc sulfate. For example, a further transition metal salt may be vaporized and then condensed onto the surface of the solid zinc sulfate. This allows the transition metal to be directly supported on the surface of the solid zinc sulfate catalyst.

[0177] As an alternative approach, the transition metal doped solid zinc sulfate can be prepared, for example, by mixing a salt of the transition metal with an aqueous zinc sulfate solution, and the transition metal doped solid zinc sulfate is prepared by co-precipitation and / or co-crystallization.

[0178] For example, a solution of a transition metal salt in an organic solvent (e.g., an alcohol such as ethanol) can be added to an aqueous solution of zinc sulfate to form a solution, after which the mixture can be subjected to one or more evaporation, distillation, precipitation and / or crystallization steps.

[0179] Any suitable apparatus can be used to carry out the evaporation, distillation, precipitation and / or crystallization steps, for example a crystallizer, such as a Swenson DTE crystallizer, can be used to obtain solid zinc sulfate doped with a transition metal.

[0180] Any suitable form of transition metal can be used with the solid zinc sulfate. For example, a salt form of the transition metal can be used. The transition metal can also or alternatively be present as an oxide. The transition metal can also or alternatively be present in the form of the metal itself. In some embodiments, the transition metal can be present in a mixture form, for example as an oxide and as the metal itself. For example, in some embodiments, the transition metal present on the surface of the solid zinc sulfate can be present as an oxide (or primarily as an oxide) and the transition metal present inside the zinc sulfate can be present as a metal (or primarily as a metal). In the case of palladium, for example, in some embodiments, palladium can be present in and / or on the solid zinc sulfate as palladium metal and / or palladium oxide.

[0181] In some embodiments, in addition to incorporating a transition metal such as palladium, iron, cobalt or nickel, a stabilizing metal salt and / or an acidity adjusting metal salt is added in an amount. Such a step may be performed to improve the efficiency of the doping process by stabilizing the transition metal, for example by forming a spinel or alloy that is stable and less prone to agglomeration upon heat treatment. Examples of stabilizing metals and / or acidity adjusting metals that can be used include lanthanum and cesium.

[0182] In some embodiments, the stabilizing metal salt and / or the acidity adjusting metal salt are introduced by impregnation onto a solid zinc sulfate support or by co-precipitation with zinc sulfate and a transition metal.

[0183] In some embodiments, solid zinc sulfate is recovered from the aqueous zinc sulfate solution prior to the mixing step with the transition metal salt and also with the stabilizing metal salt and / or the acidity adjusting metal salt.

[0184] In some embodiments, the stabilizing metal salt and / or the acidity adjusting metal salt are mixed with an aqueous zinc sulfate solution and with a salt of a transition metal, and solid transition metal doped zinc sulfate is produced by co-precipitation and / or co-crystallization.

[0185] In some embodiments, a calcination step is performed after production of the transition metal doped solid zinc sulfate, e.g., to remove impurities. Thus, in some embodiments, the method includes the step of calcining the transition metal doped solid zinc sulfate.

[0186] The calcination step may serve to provide any one or more of the following advantages: mechanically and thermodynamically stabilizing the microstructure of the transition metal doped zinc sulfate, removing other impurities or volatiles, providing transition metal doped zinc sulfate with more uniform and homogeneous dispersion, and / or enabling improved catalytic activity.

[0187] Any suitable equipment that allows for controlled calcination conditions can be used, for example a reactor such as a packed bed reactor.

[0188] The calcination step is carried out at an elevated temperature, for example, in the range of about 300 to about 1000° C. In some embodiments, the calcination step is carried out at a temperature in the range of about 400 to about 800° C., for example, about 400° C., about 500° C., about 600° C., about 700° C., or about 800° C.

[0189] The calcination step may be carried out in the presence of an inert atmosphere such as, for example, argon or nitrogen.

[0190] In some embodiments, the transition metal doped solid zinc sulfate is subjected to a reduction step after calcination by exposure to hydrogen at a temperature in the range of about 400 to about 800° C., such as in the range of about 500 to 700° C., or at about 400° C., or about 500° C., or about 600° C., or about 700° C., or about 800° C. It is believed that carrying out a reduction step may promote the production of a particularly active catalyst. Typically, the reduction step is carried out in the presence of an inert gas, such as hydrogen.

[0191] The reduction step can be carried out using any suitable apparatus, for example a packed bed reactor.

[0192] The zinc sulfate and transition metal doped solid zinc sulfate produced by the above process are utilized, for example, as catalysts for producing furfural.There is thus also provided the use of zinc sulfate produced by the process as defined herein, or the use of the transition metal doped solid zinc sulfate produced by the process as defined herein, as a catalyst for producing furfural from lignocellulosic material or fractions thereof.

[0193] Solid zinc sulfate doped with a transition metal, when used as a catalyst to produce furfural, can in some embodiments be used for a single reaction or a small number of reactions. However, in other embodiments, the catalyst can be used to produce many batches of furfural or can be used in a continuous process over an extended period of time. In some cases, after multiple uses or after a sufficient period of use, it may be desirable to treat the catalyst to regenerate and / or improve its activity, for example by subjecting it to reducing conditions as discussed above.

[0194] Thus, there is provided a method for regenerating an active transition metal doped zinc sulfate catalyst used for producing furfural from lignocellulosic material or fractions thereof, comprising subjecting the transition metal doped zinc sulfate to a reduction step, for example by exposure to hydrogen at a temperature in the range of about 400 to about 800°C.

[0195] As discussed above in connection with the method of producing solid zinc sulfate, the tire char residue may then be used as a fuel in a power plant or converted into a sorbent such as carbon black using conventional processes. Thus, in some embodiments, the method includes recovering the solid tire char residue. In some embodiments, the method includes recovering the solid tire char residue and converting the solid tire char residue into carbon black.

[0196] Zinc sulfate-rich materials and transition metal doped zinc sulfate The present disclosure also relates to zinc sulfate rich materials and catalysts thereof that are used as catalysts in the production of furfural.

[0197] Thus, in a further aspect there is provided solid zinc sulphate produced by the process defined herein.

[0198] Also provided is a transition metal doped solid zinc sulfate, wherein the transition metal is selected from the group consisting of palladium, iron, nickel and cobalt, hi some embodiments, the transition metal is palladium.

[0199] In some embodiments, the transition metal doped solid zinc sulfate comprises at least 20% zinc sulfate by weight, hi some embodiments, the transition metal doped solid zinc sulfate comprises at least 30% zinc sulfate by weight, at least 40% by weight, at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or at least 95% zinc sulfate by weight, or at least 98% zinc sulfate, or at least 99% zinc sulfate by weight.

[0200] In some embodiments, the zinc sulfate may be present in anhydrous or hydrated form. For example, in some embodiments, the zinc sulfate may be zinc sulfate heptahydrate. In some other embodiments, the zinc sulfate may be anhydrous zinc sulfate. References to wt% zinc sulfate in this disclosure refer to the wt% of the form of zinc sulfate used. For example, if zinc sulfate heptahydrate is used, the term "wt% zinc sulfate" refers to the wt% of zinc sulfate heptahydrate present in the material (e.g., present in a zinc sulfate rich catalyst).

[0201] In some embodiments, the transition metal is selected from the group consisting of palladium, iron, copper, cobalt, and nickel. In some embodiments, the transition metal is palladium or iron. In some embodiments, the transition metal is palladium.

[0202] The transition metal is typically present in an amount of up to 20% by weight. In some embodiments, the transition metal is present in an amount of about 0.1 to about 10% by weight, or about 1 to about 5% by weight, based on the total weight of the catalyst. In some embodiments, the transition metal is present in an amount of about 0.5%, about 1%, about 1.5%, about 2%, about 2.5%, about 3%, about 3.5%, about 4%, about 4.5%, or about 5% by weight.

[0203] The transition metal may be mixed with or co-precipitated with, for example, solid zinc sulfate, or the surface (or at least a portion of the surface) of the solid zinc sulfate may be coated with the transition metal.

[0204] Any suitable form of transition metal can be used with the solid zinc sulfate. For example, a salt form of the transition metal can be used. The transition metal can also or alternatively be present as an oxide. The transition metal can also or alternatively be present in the form of the metal itself. In some embodiments, the transition metal can be present in a mixture form, for example as an oxide and as the metal itself. For example, in some embodiments, the transition metal present on the surface of the solid zinc sulfate can be present as an oxide (or primarily as an oxide) and the transition metal present in the interior of the zinc sulfate rich catalyst can be present as a metal (or primarily as a metal). In the case of palladium, for example, in some embodiments, palladium can be present as palladium metal and / or palladium oxide in and / or on the solid zinc sulfate.

[0205] When the transition metal is added using a salt form of the transition metal, representative salts include nitrates, sulfates, acetates, chlorides, bromides and iodides. In some embodiments, the transition metal is added using a nitrate of the transition metal. In some embodiments, the transition metal is palladium and palladium nitrate is added to solid zinc sulfate.

[0206] In some embodiments, the transition metal doped solid zinc sulfate contains additional stabilizing and / or acidity adjusting metals, which may, for example, improve catalytic performance or stabilize the transition metal dopants present on the catalyst by forming spinels or alloys, which may make the catalyst less prone to agglomeration upon heat treatment.

[0207] Also provided herein is a transition metal doped solid zinc sulfate produced according to the process defined herein. EXAMPLES

[0208] The present disclosure is further illustrated by the following non-limiting examples.

[0209] experiment 1. Preparation of Zinc Sulfate from Scrap Tire Char Scrap tire char was derived from pyrolysis of waste scrap tires (mixture) at 800 °C in a pilot-scale fluidized bed reactor. The tire char samples were crushed, sieved to a size of 250-300 μm, and dried at 105 °C for 15 h. The internal steel and wire of the tire char were removed before washing. The elemental analysis of the scrap tire char (see Table 1) was presented in our previous study

[17] . The ash content was 13.3 wt%, with Zn as the most abundant element, followed by silicon (Si). Their compositions are 30% and 12 wt%, respectively, in the ash state. The other main metals are calcium (Ca, 4.7 wt% based on ash), aluminum (Al, 1.2 wt% based on ash), and iron (Fe, 1.0 wt% based on ash).

[0210] To recover zinc in tire char, various concentrations of sulfuric acid (1 to 5 mol / L) were mixed with the water-washed tire char at L / S ratios of 1 mL / g to 6 mL / g. All leaching experiments were carried out in a 250 mL conical flask in a water bath thermostatically controlled at 25°C to 80°C and stirred for a period of 10 to 120 min. The stirring speed was controlled at 300 rpm in all cases of this study. The slurry was then separated by filtration using a filter paper with a cut-off size of 450 μm. S4) The Zn-rich leachate was then evaporated at approximately 100°C until it was saturated. To precipitate zinc sulfate, the resulting saturated solution was transferred to a water bath. Further, the resulting solution was subjected to evaporation-precipitation cycles three times. Alternatively, the saturated solution was slowly evaporated at low pressure at 50 to 60°C and the resulting crystalline precipitate was filtered off as ZnSO4·7H2O.

[0211] [Table 1]

[0212] 2. Preparation of Zinc Sulfate Catalyst Pure ZnS, ZnO and ZnSO4 were purchased from Merck Co Ltd. A certain amount of Pd(NO3)2·2H2O (Merck) was mixed with ZnSO4·7H2O (Merck) with a liquid to solid ratio (L / S) of 10 mL / g and 30 mL ethanol in a beaker for 15 min of ultrasonic treatment. The mixture was then transferred to an autoclave for hydrothermal treatment at 180 °C for 12 h and then dried under vacuum at 80 °C. The powder was then calcined at 550 °C for 2 h for further use. The prepared catalyst was labeled as ZnSO4 / PdO with a PdO content of approximately 0.8 wt% (1.1 mol%).

[0213] 3. Furfural Production 3.1 Materials The D-allose (C6H 12 O6), D-glucose (C6H 12 O6) and xylan ((C5H 10O5) n ) was reagent grade with purity >99% and was purchased from Merck Co Ltd.

[0214] 3.2 Pyrolysis experiment Pyrolysis experiments were carried out in a Pyro-GC system using a fixed-bed quartz tubular reactor (2 mm in diameter and 30 mm in length) as previously described

[13] . Briefly, biomass components and catalyst (with and without HO) were placed in the first and second stages, respectively. The temperatures were varied in the range of 300 to 500 °C, and the carrier gas was helium (He, 26 mL / min). The retention time was set to 25 s at each end temperature. The effluent discharged from the reactor was sent to an FID detector (Agilent, 7890B) coupled with a capillary column for liquid products. The oven was ramped from 50 °C (held for 2 min) to 250 °C (held for 2 min) at 25 °C / min. The split ratio was set to 25:1. At least two replicates were performed for each condition.

[0215] 3.3 Results 3.3.1 D-Allose as a raw material Catalytic pyrolysis of D-allose (C6) at 400 °C was tested for various catalysts with a catalyst to biomass mass ratio of 4. The results are shown in Figure 1. The conditions were as follows: pyrolysis in a Pyro-GC system, feed: D-allose, pyrolysis temperature: 400 °C, heating rate: 20 °C / ms, hold time: 25 s, catalyst to D-allose mass ratio: 0 or 4, water to D-allose mass ratio: 0.

[0216] Conversion of allose increased from 70 wt% when allose was used alone to 94 wt% when ZnSO4 / PdO (0.8 wt% (1.1 mol%) PdO) catalyst was employed. Selectivity of furfural increased from 22% when allose was used alone to 30%, 34% and 48%, respectively, in the order of blank (i.e. allose alone), ZnS, ZnSO4 and ZnSO4 / PdO. In contrast, the use of ZnO or PdO promoted the production of furan in addition to furfural.

[0217] Considering that temperature strongly influences the catalytic activity, various temperatures ranging from 300 to 500 °C were tested with and without ZnSO4 / PdO as catalyst. As can be seen in Figure 2, compared with D-allose alone, the use of this catalyst increased both the conversion of D-allose and the selectivity of furfural at all tested temperatures. Notably, 400 °C was further identified as the optimal temperature for both the total conversion of allose and the selectivity of furfural.

[0218] The conditions were as follows: pyrolysis in a Pyro-GC system, raw material: D-allose, pyrolysis temperature: 300 to 500 °C with a temperature difference of 50 °C, heating rate: 20 °C / millisecond, holding time: 25 seconds, mass ratio of ZnSO4 / PdO to D-allose: 0 or 4, mass ratio of water to D-allose: 0.

[0219] In addition, various catalyst / allose ratios at 400°C were tested, as shown in Figure 3. The conditions were as follows: pyrolysis in a Pyro-GC system, raw material: D-allose, pyrolysis temperature: 400°C, heating rate: 20°C / ms, holding time: 25 s, mass ratio of ZnSO4 / PdO to D-allose: 0 to 8, mass ratio of water to D-allose: 0.

[0220] The selectivity of furfural increased linearly when 2 and 4 times the ZnSO4 / PdO catalyst was used, and increased more slowly to approximately 52% when 8 times the catalyst was used. Similarly, the conversion of allose increased from 69 wt% to 96 wt% at a catalyst to allose mass ratio of 8.

[0221] The effect of water vapor was investigated by injecting various ratios of H2O into the reactor when the mass ratio of ZnSO4 / PdO to allose was 8. The results are shown in Figure 4. The conditions were as follows: pyrolysis in a Pyro-GC system, raw material: D-allose, pyrolysis temperature: 400°C, heating rate: 20°C / ms, holding time: 25 s, mass ratio of ZnSO4 / PdO to D-allose: 8, mass ratio of water to D-allose: 0 to 20.

[0222] It was found that steam promoted the formation of levulinic acid (LA). While the production of light compounds (LC) was hindered by steam, the furfural selectivity interestingly showed an increasing trend as the steam to allose ratio increased to 10:1. At a steam to allose ratio of 10, the conversion of allose was 92 wt% and the selectivity of furfural was about 56%.

[0223] 3.3.2 D-glucose as a raw material Zinc sulfate catalysts were also evaluated for their ability to convert glucose to furfural. As demonstrated in Figure 5a, ZnSO4 / PdO was also found to be the best catalyst in terms of selectivity of furfural from glucose, similar to the catalytic performance of D-allose. The conditions used were as follows: pyrolysis in Pyro-GC system, feed: D-glucose, pyrolysis temperature: 400°C, heating rate: 20°C / ms, holding time: 25 s, mass ratio of catalyst to D-glucose: 0 to 8, mass ratio of water to D-glucose: 0.

[0224] By increasing the catalyst to glucose ratio, the furfural selectivity increased from 23% for glucose alone to 43% for the ZnSO4 / PdO catalyst at a mass ratio to glucose of 8:1, as shown in Figure 5b. The furfural selectivities for glucose and allose were similar to those without catalyst, 23% and 22%, respectively.

[0225] Thermogravimetric analysis (TGA, see FIG. 6) showed that when ZnSO4 / PdO catalyst was used, the decomposition temperature was reduced by 30° C. for glucose compared to 127° C. for allose. This result supports that ZnSO4 / PdO is a particularly good catalyst when using allose as a raw material.

[0226] 3.3.4 Xylan as a raw material The use of zinc sulfate catalyst to catalyze the conversion of allose to furfural was also investigated. Unlike the case of D-glucose (C6) and D-allose (C6) as feedstocks, where ZnSO4 / PdO had the highest catalytic activity in the production of furfural, pure ZnSO4 was found to be the best catalyst when xylan (C5) was used as feedstock (see Figure 7). The conditions used were: pyrolysis in a Pyro-GC system, feedstock: xylan, pyrolysis temperature: 400°C, heating rate: 20°C / ms, holding time: 25 s, mass ratio of catalyst to xylan: 4, mass ratio of water to xylan: 0 or 10.

[0227] The conversion of xylan was found to be close to 100% when ZnSO4 or ZnSO4 / PdO catalysts were used. Furthermore, when ZnSO4 catalyst was used, the selectivity of furfural increased from 36% for xylan alone to 72% with ZnSO4 catalyst at catalyst:xylan mass ratios from 4 to 1. The furfural selectivity was further improved to 87% when the catalyst to xylan mass ratio was 10:1 and steam was added.

[0228] 3.3.5 Real biomass as feedstock – sugarcane bagasse and corn cobs ZnSO4 and Pd-containing ZnSO4 catalysts were also tested using real biomass including sugarcane bagasse (see Table 2) and corn cobs (see Table 3).

[0229] For sugarcane bagasse, ZnSO4 / PdO(0.4) gave the highest amount of furfural at 22.8 wt% with a selectivity of 44 area % at 400 °C and a water to sugarcane bagasse mass ratio of 10. This furfural yield is about two times higher than the yield of 8 to 11 wt% reported using Westpro / Huaxia Technology

[14] . At the same time, 14.6 wt% of acetic acid could be produced.

[0230] For corncob, 32.2 to 32.9 wt% furfural was obtained with a catalyst containing 0.4 to 1.1 mol% PdO (ZnSO4 / PdO) at a water to corncob mass ratio of 10. This furfural yield is about three times higher than the 10 to 12 wt% reported by Westpro / HuaxiaTechnology.

[14] The overall liquid yield was in the range of 65.0 to 69.1 wt%, and the furfural selectivity varied from 58.8 to 61.2 area %. The main by-product was acetic acid, at 12.5 to 13.7 wt%.

[0231] The conditions used were as follows: pyrolysis in a Pyro-GC system, feedstock: sugarcane bagasse or corn cob, pyrolysis temperature: 400°C, heating rate: 20°C / ms, holding time: 25 s, catalyst to biomass mass ratio: 8, water to biomass mass ratio: 0 or 10.

[0232] [Table 2]

[0233] [Table 3]

[0234] 4. Conclusion This study reported a novel method for producing zinc sulfate from waste materials via a simple process involving treating scrap tire char with sulfuric acid and isolating solid zinc sulfate from the leachate.

[0235] This study also reported novel PdO-supported and PdO-unsupported ZnSO4 catalytic systems, their preparation methods, and the use of said catalysts in the preparation of furfural from various biomass components by flash pyrolysis at 300-500 °C. For C6 sugars, ZnSO4 / PdO was found to be the best catalyst compared to other catalysts in this study. The D-allose conversion is 83.3 wt% at 400 °C with furfural selectivity of about 56% when ZnSO4 / PdO is used as catalyst with steam (steam to allose = 10:1 by mass).

[0236] When D-glucose was used as the raw material, the furfural selectivity was 43% and the light compounds (LC) was 28.3% at a D-glucose conversion of 90% using ZnSO4 / PdO as the catalyst.

[0237] For the C5 sugar xylan, ZnSO4 was found to be the best catalyst, with furfural selectivity increasing from 36% with xylan alone to 72% with ZnSO4 catalyst, and further up to 87% with steam (steam to xylan = 10:1 by mass). Xylan conversion was close to 100% when ZnSO4 or ZnSO4 / PdO was used as catalyst.

[0238] For real biomass feedstocks, sugarcane bagasse and corn cob, 22.8 and 32.9 wt% furfural were obtained, respectively, using ZnSO4 / PdO catalyst at a steam to biomass mass ratio of 10.

[0239] reference

[0240] [Table 4] The entire contents of each of the above references are incorporated herein by reference in their entirety.

Claims

1. 1. A method for producing furfural, comprising pyrolyzing a lignocellulosic material or a fraction thereof and producing furfural, wherein the production of furfural is catalyzed by a solid zinc sulfate rich catalyst.

2. 10. The method of claim 1, wherein the catalyst comprises at least 50% by weight zinc sulfate.

3. 2. The process of claim 1, wherein the solid zinc sulfate rich catalyst contains an additional transition metal.

4. 4. The method of claim 3, wherein the further transition metal is palladium, iron, copper, cobalt or nickel.

5. 4. The process of claim 3, wherein the solid zinc sulfate rich catalyst contains palladium metal and / or palladium oxide.

6. 5. The process of claim 4, wherein the solid zinc sulfate rich catalyst contains from 0.2 to 5 wt. % of a further transition metal.

7. 2. The method of claim 1, wherein the lignocellulosic material or fraction thereof is selected from the group consisting of wood chips, sawdust, sugar cane, corn cobs, bagasse, oat hulls, cottonseed hulls, rice hulls and wheat bran, cellulose and hemicellulose fractions, and mono-, di- and oligosaccharides.

8. Prior to pyrolysis, the lignocellulosic material or a fraction thereof may be - removing the lignin fraction, and / or - Hydrolyzes sugar bonds The method of claim 1 , further comprising one or more pre-processing steps.

9. 2. The method of claim 1, wherein the production of furfural is carried out in the absence of steam.

10. 10. The method of claim 9, wherein the production of furfural is carried out in the presence of steam, and the weight ratio of steam to the lignocellulosic material or fraction thereof is within the range of about 0.1:1 to about 20:1, in some cases about 8:1 to about 20:

1.

11. 10. The method of claim 1, wherein the pyrolysis and / or production of furfural is carried out at a temperature in the range of about 300 to about 500°C.

12. 10. The method of claim 1, carried out as a batch process or as a continuous or semi-continuous process.

13. 10. The method of claim 1 including the step of separating the furfural from other reaction products.

14. 1. A method for producing one or more of furfuryl alcohol, furoic acid, furan, tetrahydrofuran, levulinic acid, butadiene, hexamethylenediamine, tetrahydrofurfuryl alcohol, methyltetrahydrofuran, and furfural phenolic resins, comprising the steps of: Producing furfural according to the method of any one of claims 1 to 13; converting the furfural to furfuryl alcohol, furoic acid, furan, tetrahydrofuran, levulinic acid, butadiene, hexamethylenediamine, tetrahydrofurfuryl alcohol, methyltetrahydrofuran, and furfural phenolic resin; The method comprising:

15. 1. A method for producing solid zinc sulfate comprising the steps of: contacting the tire char with an aqueous sulfuric acid solution and producing a mixture of an aqueous zinc sulfate solution and solid tire char residue; separating the aqueous zinc sulfate solution from the solid tire char residue; recovering solid zinc sulfate from the aqueous zinc sulfate solution; The method comprising:

16. 1. A method for producing transition metal doped zinc sulfate comprising the steps of: contacting the tire char with an aqueous sulfuric acid solution and producing a mixture of an aqueous zinc sulfate solution and solid tire char residue; separating the aqueous zinc sulfate solution from the solid tire char residue; recovering solid zinc sulfate from the aqueous zinc sulfate solution; contacting the zinc sulfate with a further salt of a transition metal; producing a solid zinc sulfate doped with a transition metal; The method comprising:

17. 17. The method of claim 16, wherein the further transition metal is palladium, iron, cobalt or nickel.

18. 17. The method of claim 16, comprising calcining the transition metal doped solid zinc sulfate.

19. 20. The method of claim 18, wherein the transition metal doped solid zinc sulfate, after calcination, is subjected to a reduction step by exposure to hydrogen at a temperature in the range of about 400 to about 800°C.

20. 1. A method for regenerating an active transition metal doped zinc sulfate catalyst used for producing furfural from lignocellulosic material or fractions thereof, comprising subjecting the transition metal doped zinc sulfate to a reduction step by exposure to hydrogen at a temperature in the range of about 400 to about 800°C.

21. A transition metal doped solid zinc sulfate, wherein the transition metal is selected from the group consisting of palladium, iron, nickel and cobalt.